Evi1 upregulates Fbp1 and supports progression of acute myeloid leukemia through pentose phosphate pathway activation. Issue 10 (22nd August 2021) - Mizuno, Hideaki; Koya, Junji; Masamoto, Yosuke; Kagoya, Yuki; Kurokawa, Mineo
Abstract: Evi1 is a transcription factor essential for the development as well as progression of acute myeloid leukemia (AML) and high Evi1 AML is associated with extremely poor clinical outcome. Since targeting metabolic vulnerability is the emerging therapeutic strategy of cancer, we herein investigated a novel therapeutic target of Evi1 by analyzing transcriptomic, epigenetic, and metabolomic profiling of mouse high Evi1 leukemia cells. We revealed that Evi1 overexpression and Evi1‐driven leukemic transformation upregulate transcription of gluconeogenesis enzyme Fbp1 and other pentose phosphate enzymes with interaction between Evi1 and the enhancer region of these genes. Metabolome analysis using Evi1‐overexpressing leukemia cells uncovered pentose phosphate pathway upregulation by Evi1 overexpression. Suppression of Fbp1 as well as pentose phosphate pathway enzymes by shRNA‐mediated knockdown selectively decreased Evi1‐driven leukemogenesis in vitro. Moreover, pharmacological or shRNA‐mediated Fbp1 inhibition in secondarily transplanted Evi1‐overexpressing leukemia mouse significantly decreased leukemia cell burden. Collectively, targeting FBP1 is a promising therapeutic strategy of high Evi1 AML. Abstract : The activated pentose phosphate pathway enhances progression of Evi1‐overexpressing leukemia. Fbp1 and other glucose metabolism‐related genes cooperatively upregulate pentose phosphate pathway activity.